Oxidation of melatonin by taurine chloramine - Ximenes, Valdecir Farias [UNESP]; Padovan, Camila Z. [UNESP]; Carvalho, Danielle A. [UNESP]; Fernandes, João Roberto [UNESP] (Wiley-Blackwell, 2010)
Melatonin is widely known for its antioxidant, immunomodulatory, and anti-inflammatory effects. Hypochlorous acid (HOCl) is one example of an endogenous oxidant that is promptly neutralized by melatonin. Melatonin also inhibits myeloperoxidase, the enzyme that catalyzes the oxidation of chloride to HOCl. Taurine is the most abundant free amino acid in leukocytes. In activated neutrophils, taurine is converted to taurine chloramine (Tau-NHCl) through a reaction with HOCl. In addition, the related compound taurine bromamine (Tau-NHBr) can be released by neutrophils and eosinophils. The aim of this study was to investigate the reactivity of Tau-NHCl and Tau-NHBr with melatonin. We found that melatonin can react with either Tau-NHCl or Tau-NHBr, leading to the production of 2-hydroxymelatonin and N1-acetyl-N2-formyl-5-methoxykynuramine (AFMK). The reaction was pH-dependent, and it occurs more rapidly at a slightly acidic pH. Tau-NHBr was significantly more reactive than Tau-NHCl. Using Tau-NHBr as the oxidizing agent, 1 mm melatonin was oxidized in less than 1 min. The pH dependence of the reaction with Tau-NHCl and the increased reactivity of Tau-NHBr can be explained by a mechanism based on the initial attack of chloronium (Cl+) or bromonium (Br+) ions on melatonin. We also found that the addition of iodide to the reaction medium increased the yield of AFMK. These findings could contribute to the establishment of new functions for melatonin in inflammatory and parasitic diseases, where the role of this indoleamine has been extensively investigated.
Keywords: melatonin; N1-acetyl-N2-formyl-5-methoxykynuramine (AFMK); taurine; taurine bromamine; taurine chloramine